Role of Social Capital in Creative Economy Development in the Craft Sub-Sector in the Tourism Destination Area of Sawahlunto City, West Sumatra Province - Latifah Izzatul Jannah; Zusmelia Zusmelia; Irwan Irwan (Universitas of Muhammadiyah Makassar, 2024)
This research is based on the background that creative economic actors in the craft sub-sector in Sawahlunto City network cooperation in the sale of crafts not only in Indonesia but has spread outside Indonesia one of them Malaysia, Japan and Singapore, China and some others. In addition, social capital in the development of the creative economy can increase group members to cooperate in the development of the creative economy. This study aims to analyze the role of social capital in the development of the creative economy of the craft sub-sector in Sawahlunto City. The theory used is the theory of Ledogar Fleming, 2008. This research uses a qualitative approach with descriptive type. The technique of withdrawing informants in this study was carried out by purposive sampling technique. Data collection methods were carried out by document study, non-participant observation and in-depth interviews. The data analysis used was interactive data analysis developed by Milles and Huberman (1992). The results of this study indicate that the development of the creative economy of the craft sub-sector in Sawahlunto City has gained the trust of the community for the products produced. This shows that the involvement of actors has a role in strengthening social capital. Social capital carried out by creative economic actors in the craft sub-sector in Sawahlunto City is expanding the access network of creative economic actors, the ability to engage in forming joint actions and building trust in forming cooperation in the creative economic development of the craft sub-sector in the tourist destination area of Sawahlunto City.From the explanation, it can be concluded that social capital has an important role in the development of the creative economy in the craft sector. The Novelty in this research is social capital as access to social action.